The influence of financial technology & literacy on MSMEs sustainability with financial inclusion as a mediating variable - Noor Endah Cahyawati; Kacahya Hanugrah Nantungga; Yunice Karina Tumewang (Journal of Contemporary Accounting, 2023)
Micro and Small Enterprises (MSMEs) contribute a major share to the regional economy. In recent times, business competitiveness grows precariously making sustainability a problem. This study aims to provide empirical evidence about the relationship between financial technology, literacy, inclusion, and MSMEs’ sustainability in Sleman. This study uses a quantitative approach with Partial Least Square (PLS). Data were collected from questionnaires of 100 MSMEs in Sleman with a convenience sampling technique. The results reveal that financial technology and literacy impose a positive effect on financial inclusion, while financial technology and literacy exert a positive effect on MSMEs’ sustainability. In addition to that, financial inclusion is also found to have a positive effect on mediating financial technology and literacy influence on MSMEs’ sustainability. This study provides input for MSMEs management to increase the use of financial technology to support MSMEs’ sustainability and for the local government to promote financial literacy for MSMEs and enhance financial inclusion which will ultimately advance MSMEs’ sustainability.